Basic Assumptions of the Theory of Borrowing - Mańczak-Wohlfeld, Elżbieta (Armenian Folia Anglistika, 2006)
The article highlights the three methods of vocabulary enlargement – the creation of neologisms, changes in the word meaning and borrowings. Borrowings or loan-words are, first of all, introduced by bilinguals and acquire an increasingly wider usage in the given language. Therefore, the author of the article concludes that borrowing is a dynamic process since the word becomes a constituent of the language system once it is used in speech.The article also addresses a number of issues related to the efficiency of borrowings, as well as their assimilation in the recipient language.